Dog Care - Fogle, Bruce (New York Dorling Kindersley, 1995)
Core information on caring for dogs is reduced to the 101 most crucial facts you must know. The pocket-size paperback format makes it ideal for quick reference.
Include Color Illustration and Index
Keywords: Dogs -- Pets